Missing Black males among preterm births in the US, 1995 to 2019 - Bruckner, Tim A.; Chakrabarti, Suman; Bustos, Brenda; Catalano, Ralph; Gemmill, Alison; Casey, Joan A.; Lee, Hedwig (2024)
Background In the US, non-Hispanic (NH) Black birthing persons show a two-fold greater risk of fetal death relative to NH white birthing persons. Since males more than females show a greater risk of fetal death, such loss in utero may affect the sex composition of live births born preterm (PTB; <37 weeks gestational age). We examine US birth data from 1995 to 2019 to determine whether the ratio of male to female preterm (i.e., PTB sex ratios) among NH Black births falls below that of NH whites and Hispanics.